Unsteady convective boundary layer of a Nano fluid over a stretching sheet in the presence of Viscous dissipation, Chemical reaction & Porous Medium. (2017) - Achi Reddy, Ch; Shankar, B.
Abstract: The attempt made in the paper is to study heat and mass transfer modelled in the boundary-layer flow of unsteady viscous Nano fluid along a vertical stretching porous sheet. The analysis of viscous dissipation and chemical reaction of the proposed fluid has been presented in the paper. The governing boundary layer equations are reduced to ordinary differential equations by the similarity transformations. Numerical solutions of these equations are obtained by a finite difference scheme, known as the Keller box method. The simulation of velocity profile, rate of heat and mass transfer has been made and the graphical presentation of the results is shown in the paper.